BUILDING MARKETING PERFORMANCE THROUGH COMPETITOR ORIENTATION (Empirical Study on Baitul Maal wat Tamwil at Ex-Residency of Semarang) - Isywari, Citra Ajeng; Ferdinand, Augusty Tae; Indriani, Farida (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2018)
This research specifically examines the effect of competitor orientation on marketing performance through service value co-creation quality, service innovation capability and service value proposition. The object of this research is Baitul Maal wat Tamwil (BMT) in ex-Residency Semarang, Central Java, Indonesia. This research is analyzed with Structural Equation Model (SEM) using AMOS software. Based on the result of the research, it can be concluded that competitor orientation positively and significantly can affect the service value co-creation quality and service innovation capability owned by BMT. Service value co-creation quality positively and significantly can affect the service innovation capability and marketing performance of BMT. Service innovation capability positively and significantly influences the service value proposition and service value proposition positively and significantly can influence BMT’s marketing performance.